Financial feasibility of restoring post-mined land using oil palm plantation in Ghana: multi-stakeholder validation workshop - Tilahun, Seifu A.; Ametefe, D. L.; Atampugre, Gerald; Oke, Adebayo; Bobtoya, Saadia; Danso, F. (International Water Management Institute, 2025)
This report assesses the financial feasibility of restoring degraded post-mined lands in Ghana through large-scale oil palm plantations. Building on a 22-acre pilot site reclaimed in 2024 under the CGIAR Initiative on West and Central African Food Systems Transformation, the CGIAR Scaling for Impact Program analyzed costs, returns, and sustainability prospects for scaling up oil palm cultivation across 39,500 acres of abandoned land. Findings from initial analysis indicate that oil palm, valued for its resilience and multiple revenue streams, can achieve profitability within three years and generate substantial long-term returns when combined with intercropping, by-product use, and carbon credits. A stakeholder validation workshop in Accra, however, emphasized the need to reassess assumptions on reclamation costs, fresh fruit bunch yields, early maturity timelines, and to strengthen environmental safeguards and policy alignment. While the preliminary results show strong potential for oil palm-based reclamation to restore post-mined land, create jobs, and improve livelihoods, a revised financial analysis is required to incorporate stakeholder feedback and ensure risks are managed through transparent, inclusive, and sustainable frameworks.